Assessment of the Evolving Role of Real Estate Agents (REAs) and Customer Preferences Towards Home Buying - Ahmad Halim, Aini Najihah; Ishak, Mohd Hafizal; Md Yassin, Azlina; Ahmad, Nurul Afiqah; Masram, Haidaliza; Thanaraju, Puvaneswary A/P (Research in Management of Technology and Business, 2026)
Real estate agents are registered professionals who connect buyers and sellers. Their primary purpose is to help clients make informed decisions while navigating the intricacies of real estate transactions. Nowadays, evolving customer needs in real estate are essential to the success and sustainability of any organisation. Customer preferences, needs, and behaviours are constantly changing due to various factors such as technological advances, cultural shifts, economic changes, and social trends. Thus, this research was undertaken to study the evolving role of real estate agents (REA) and customer preferences toward home-buying decisions, and to analyse the relationship between the evolving role of real estate agents (REA) and customer preferences. All data is analysed using content analysis to respond to real estate agents and customers. The role of a real estate agent lies in their professional practice, guaranteeing customer satisfaction, as it is essential to establish long-term relationships and encourage good word-of-mouth referrals. Finally, this study contributes to the development of real estate agents' roles and client preferences, aiming to strengthen long-term connections in house purchasing decisions and provide better home marketing any sales.